Hematological Study in Three Lines of Quail and Their Crosses - Meshabaz, Ronak A.; Sulaiman, Kurdman M.; Hussen, Shekhmous H.; Berwary, Mwafaq S.; Saleh, Jamila S.; Ahmed, Saif A.; Mohammed, Najat J. (Science Journal of University of Zakho, 2017)
The present study was conducted at poultry laboratories, department of animal production, Agriculture College, Duhok University, Kurdistan region, Iraq, (2016). Three lines of quail (White, light brown and dark brown) and their crosses that resulted from diallel cross design; aged 8 weeks old were used. A total of 54 blood samples by about 5 ml, from both sexes within each genotype aged 8 weeks old, were collected directly after slaughtering and bleeding for 3 second. PVC %, hemoglobin (Hb), Hetrophyl (H), Lymphocyte (L), H/L ratio, total protein, globulin, albumen and cholesterol were studied. The results showed insignificant differences among genotypes and between sexes for both PVC and Hb, while H, L, H/L, total protein, globulin, albumen and cholesterol appeared high significant (p<0.01) differences among the nine studied genotypes. The effect of sex was significant (p<0.05) for H, L and cholesterol. Interaction between genotype and sex was just significant for albumen. There was a significant negative correlation between H/L ratio and globulin (-0.39). Dependence of H/L ratio on globulin, resulted in derives a prediction equation.